Genetic diagnosis of common fetal renal abnormalities detected on prenatal ultrasound. (5th May 2022) - Liu, Ling; Li, Juan; Li, Ying; Li, Haiyu; Yang, Bo; Fan, Hui; Wang, Jing; Gu, Yanting; Yu, Hui; Bai, Maohuan; Yu, Tantan; Cui, Shihong; et al.
Abstract: Objectives: This retrospective study aimed to investigate the correlations between phenotypes of fetal renal abnormalities on prenatal ultrasound and genetic aetiologies detected using chromosomal microarray analysis (CMA) and whole‐exome sequencing (WES). Methods: Fetuses with renal abnormalities were subjected to CMA and were further analysed by WES when CMA‐negative. The detection rates for chromosomal abnormalities and monogenic variants among different types of isolated renal abnormalities and those with extrarenal abnormalities (non‐isolated cases) were determined and compared. Results: CMA detected chromosomal abnormalities in 78 of 577 fetuses (13.52%). WES detected monogenic variants in 31 of 160 fetuses (19.38%) that had non‐diagnostic CMA results. In cases of isolated hyperechogenic kidney, polycystic kidney disease, and multicystic dysplastic kidney, the detection rates of copy number variants (CNVs) by CMA and monogenic variants by WES were not significantly different ( p > 0.05). However, monogenic variants were more frequently detected than CNVs when kidney abnormalities were accompanied by reduced amniotic fluid ( p < 0.05). Other renal abnormalities identified on prenatal ultrasound had different detection rates. Conclusions: Our findings contribute to the overall knowledge of genetic variants associated with prenatally identified renal anomalies and may aid in decision making regarding prenatal genetic testing options for affected pregnancies. Key points: What's already known about this topic? Fetal renal abnormalities are some of the common and most easily detectable anomalies on ultrasound. The disease has a wide range of prenatal phenotypes with distinct prognoses and etiologies. Studies have shown that fetal renal abnormalities may be related to certain genetic disorders or syndromes. However, one of the major challenges to the use of genetic information in the clinical setting remains the lack of strict genotype‐phenotype correlation. What does this study add? This study first explored the correlations between phenotypes of fetal renal abnormalities detected on prenatal ultrasound and genetic aetiologies detected by CMA and WES. Our results suggest that hyperechogenic kidney should be confirmed with genetic testing. Renal abnormalities presenting together with reduced AF are likely to be related to monogenic variants. Genetic abnormalities in cases with obstructive renal dysplasia and duplex kidney were rarely observed.